Neurotized Free Platysma Flap for Functional Eyelid Reconstruction: A Cadaveric Study of Anatomical Feasibility. Issue 4 (April 2020) - Vaca, Elbert E.; Surek, Christopher; Klosowiak, Julian; Dumanian, Gregory A.; Alghoul, Mohammed S.
Abstract : Background: Conventional reconstructive options for large full-thickness eyelid defects are limited to static local flaps without replacing the missing orbicularis. The authors' aim is to delineate the platysma neurovascular anatomy for innervated functional eyelid reconstruction. Methods: Fourteen fresh latex-injected heminecks were dissected. The locations where neurovascular structures entered the platysma muscles were expressed as the percentage distance ± SD from the sternocleidomastoid muscle mastoid insertion to manubrium origin. Results: The superior thyroid, facial, and lingual vessels were the major pedicles in eight of 14 (57.1 percent), four of 14 (28.6 percent), and one of 14 specimens (7.1 percent), respectively. In one specimen (7.1 percent), both the superior thyroid and facial vessels supplied a major pedicle. Venous drainage generally mirrored arterial inflow but was redundant, with 43 percent and 14 percent of flaps also with major contributions from the external jugular and anterior jugular veins, respectively. Neurovascular pedicles entered the platysma 28 to 57 percent caudal to the sternocleidomastoid muscle mastoid insertion, between 0.5 and 4.8 cm anterior to the medial sternocleidomastoid muscle border. Conclusion: Although variability exists, platysma neurovascular pedicles enter at predictable locations between 28 and 57 percent of the distance from the mastoid insertion of the sternocleidomastoid muscle, therefore making free platysma transfer a feasible option for eyelid reconstruction.